2020
DOI: 10.3390/ma13173781
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Flexible Wearable Antenna Sensors: Design, Fabrication Methods, and Applications

Abstract: This review paper summarizes various approaches developed in the literature for antenna sensors with an emphasis on flexible solutions. The survey helps to recognize the limitations and advantages of this technology. Furthermore, it offers an overview of the main points for the development and design of flexible antenna sensors from the selection of the materials to the framing of the antenna including the different scenario applications. With regard to wearable antenna sensors deployment, a review of the text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 93 publications
0
49
0
Order By: Relevance
“…[65] Because of this, the industry and academia have developed a strong interest in flexible sensors, and scientists have begun to improve their mechanical properties, including tensile properties, deformation properties, and biocompatibility, so that they can be used in various parts of the human body. [66] Due to the flexibility, extensibility and mechanical strength of cellulose hydrogels, it has become an ideal substrate for motion conduction. [67] For cellulose aerogels, porous aerogel materials have low density, high sensitivity and good mechanical properties.…”
Section: Application Of Cellulose Gel In Flexible Sensingmentioning
confidence: 99%
“…[65] Because of this, the industry and academia have developed a strong interest in flexible sensors, and scientists have begun to improve their mechanical properties, including tensile properties, deformation properties, and biocompatibility, so that they can be used in various parts of the human body. [66] Due to the flexibility, extensibility and mechanical strength of cellulose hydrogels, it has become an ideal substrate for motion conduction. [67] For cellulose aerogels, porous aerogel materials have low density, high sensitivity and good mechanical properties.…”
Section: Application Of Cellulose Gel In Flexible Sensingmentioning
confidence: 99%
“…Regarding the materials used for flexible antennas, there are very different technologies such as conductive wires or fabrics [10] [11], silver paste [12] or conductive inks [13] which make it possible to achieve the radiating element of the antenna. To constitute the flexible substrate, one can find polyester [14] or polymers using fibers such as cotton or felt [12] but also polydimethylsiloxane (PDMS) or graphene (FGF) [15] films. These different materials have different costs and performance and must combine reliability, robustness, sturdiness and flexibility.…”
Section: Antenna Design and Materials Characteristicsmentioning
confidence: 99%
“…Recently, antennas operating as sensors established a growing demand for monitoring blood glucose levels [15]. Several studies have been reported in the literature using antenna-based sensors to detect blood glucose levels [16][17][18].…”
Section: Introductionmentioning
confidence: 99%